Exploring the impact of national system of innovation on the outcomes of foreign direct investment. (29th June 2009) - Baskaran, Angathevar; Muchie, Mammo
This paper attempts to explore the possible relationship between the characteristics of a National System of Innovation (NSI) and their impact on Foreign Direct Investment (FDI) outcomes, particularly in developing countries. We employ a heuristic NSI-FDI conceptual framework linking the robustness of NSI to the benefits or lack of it from FDI. We create a taxonomy of NSIs as well-functioning/strong, relatively well-functioning and weak and try to empirically find out how each NSI type is related to the corresponding FDI outcomes. We examine whether a strong NSI can bring a high-end benefit from FDI, whether those with a weak NSI are at the low end of the FDI potential benefit spectrum, and whether a relatively well-functioning NSI is linked to medium or average FDI outcomes. We used descriptive data from selected developing economies – China, India, South Africa, Ghana, Ethiopia, Tanzania and Zambia – and applied this conceptual framework. Despite some data limitations, our case studies show that the characteristics and robustness (or lack of robustness) of NSI can impact on how FDI flows to a country and the kinds of outcomes it will produce, other things being equal. Therefore, how countries build their NSI matters significantly to national policy making.